Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Turnover intention Karyawan di PT Indosato Jaya Makmur - Yusman Oktavian; Purwatiningsih Purwatiningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
PT. Indosato Jaya Makmur is a company engaged in the culinary sector through the operation of a family restaurant called Washoku Sato, which serves authentic Japanese cuisine. The company is committed to maintaining taste quality, hygiene, and production consistency by utilizing mostly locally sourced raw materials. However, the company faces a serious challenge in the form of high employee turnover intention, which can negatively affect operational continuity, team stability, and service quality. This study aims to analyze the influence of workload (X1) and job satisfaction (X2) on turnover intention (Y). A quantitative research approach was employed, with data collected through the distribution of Likert-scale questionnaires to 86 permanent employees as respondents. The data were analyzed using a series of statistical tests, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The findings reveal that workload has a positive and significant effect on turnover intention, indicating that the higher the workload perceived by employees, the greater their tendency to leave the company. Conversely, job satisfaction has a negative and significant effect, suggesting that higher job satisfaction reduces the likelihood of turnover intention. Simultaneously, both independent variables significantly influence turnover intention, with an Adjusted R² value of 35.6%, while the remaining 64.4% is influenced by other factors not examined in this study. These findings emphasize the importance of balanced workload management and continuous efforts to improve job satisfaction in order to minimize turnover intention and support the company’s operational sustainability.